2017
DOI: 10.1016/j.landurbplan.2017.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the spatial arrangement of trees in residential neighborhoods for better cooling effects: Integrating modeling with in-situ measurements

Abstract: A B S T R A C TTrees have long been recognized as effective for mitigating urban heat islands by reducing air temperature through evapotranspiration and intercepting shortwave radiation that heat up land surfaces. Many studies have shown that both the composition and configuration of vegetation can contribute to heat reduction at the city scale. Fewer studies, however, have focused on cooling mechanisms at the neighborhood scale. Here, we integrate modeling with in situ measurements to investigate how differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(47 citation statements)
references
References 42 publications
(53 reference statements)
3
33
0
1
Order By: Relevance
“…Tan et al (2015) noted that shade was the main factor providing the cooling effect of trees (Tan et al, 2015). Wu and Chen (2017) certified that trees had effects on the interception of shortwave radiation and reasonable heat abatement (Wu and Chen, 2017). Furthermore, the cooling effect of the park might be due to evapotranspiration and the higher albedo of green vegetation, which retains less solar heat and lower ambient temperatures than do impervious surfaces (Shahmohamadi et al, 2011).…”
Section: Comfort Degree On Building Area and Olympic Parkmentioning
confidence: 99%
“…Tan et al (2015) noted that shade was the main factor providing the cooling effect of trees (Tan et al, 2015). Wu and Chen (2017) certified that trees had effects on the interception of shortwave radiation and reasonable heat abatement (Wu and Chen, 2017). Furthermore, the cooling effect of the park might be due to evapotranspiration and the higher albedo of green vegetation, which retains less solar heat and lower ambient temperatures than do impervious surfaces (Shahmohamadi et al, 2011).…”
Section: Comfort Degree On Building Area and Olympic Parkmentioning
confidence: 99%
“…The acquired results revealed a maximum summer T air reduction, ranging between 2.1 • C and 5.0 • C, depending on the examined vegetation scenario, while a significant decrease of T mrt , even up to 35.0 • C, has been also achieved, due to the radiation control by the trees' foliage. In the same context, Wu and Chen [112] have investigated the effect of increasing the GCR by 10% in areas having different surface densities in Beijing, China on the local microclimatic conditions. A reduction on the peak T air between 0.20 • C and 0.50 • C was found, under summer conditions, while the average diurnal T air decrease did not exceed 0.10 • C in all cases.…”
Section: Adding Street Trees and Hedgesmentioning
confidence: 99%
“…The research also found that trees were planted in high density areas are more effective in improving thermal comfort condition than those were planted in open spaces. Some studies regarding urban trees suggested that arrangement of trees led to sensible heat reduction and temperature variation [19,48]. Although trees bring positive impact to the environment, especially on the microclimate and thermal comfort, trees can also act as barriers and decrease wind speed, which ultimately will increase heat stress at a pedestrian level [37,46].…”
Section: Treesmentioning
confidence: 99%
“…University campuses were frequently used as field measurement areas [18,84,89,90]. Some of the studies were performed in residential areas [19,45,61], heritage sites/old city [81,91], urban parks [20] and coastal area [66].…”
Section: Figure 3 Distribution Of Reviewed Envi-met Studies By Year mentioning
confidence: 99%
See 1 more Smart Citation